PENGGUNAAN MEDIA PERMAINAN TRADISIONAL BETHIK UNTUK MENINGKATKAN PEMAHAMAN PESERTA DIDIK DALAM MATA PELAJARAN MATEMATIKA PERKALIAN KELAS II MI/SD - Agus Ma'ruf (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2019)
Mathematics has an important role in various disciplines and develops students’ thinking power. The effort of the teacher in carrying out his duties as an educator certainly requires the teacher to be innovative in carrying out mathematics learning so that it does not seem boring and difficult. One of the things that needs to be considered by the teacher is the use of instructional media so students want to be active and learn with joy. Multiplication is complicated helpful material in mathematics learning to increase the understanding of teacher students needing the right media to be applied in learning, one of which is using bethik traditional game media.